Relation Between Unconjugated Bilirubin and Peripheral Biomarkers of Inflammation Derived From Complete Blood Counts in Patients With Acute Stage of Schizophrenia - Xu, Haiting; Wei, Yanyan; Zheng, Lina; Zhang, Hua; Luo, Tangren; Li, Hongjuan; Ma, Jinbao; Chen, Jingxu (Frontiers in Psychiatry, 2022)
Background: Inflammation and oxidative stress are the major leading hypothetical causes of schizophrenia. Unconjugated bilirubin (UCB) is an efficient endogenous plasma antioxidant. Inflammation is closely linked to oxidative stress .The relationship between UCB and inflammatory markers should be paid close attention in schizophrenia acute stage. Combined UCB and inflammatory markers was assessed for its ability to predict schizophrenia in the acute stage in order to find a easy and effective indicator to identify acute schizophrenia. Methods: A total of 6937 acute schizophrenia patients and 6404 health controls (HC) were enrolled. UCB and peripheral biomarkers of inflammation derived from complete blood counts (CBC) were investigated in the subjects with acute Schizophrenia and the results were compared with HC. Simultaneously, Spearman test was used to assess the correlation between variables, while logistic regression was used to determine the combined equation and receiver operating characteristic curve (ROC) was used to evaluate the combined value of UCB and peripheral biomarkers of inflammation derived from CBC to predict schizophrenia in the acute stage. Result : The study indicates that WBC, Neutrophil , monocyte, MPV, RDW, NLR, MLR have significantly increased in schizophrenia (P＜0.05 for all ) , while platelet, Lymphocyte, PLR in schizophrenia have significantly decreased (P＜0.05 for all ). UCB exhibits negative correlation with MPV significantly (r = 0.121, P <0.001). And there is no correlation between UCB and Neutrophil, monocyte. The correlations between UCB and other peripheral biomarkers of inflammation derived from CBC are very weak. MPV, RDW, NLR, MLR, PLR and UCB were taken as independent variables to make a logistic regression analysis. The model was: logit (P1)=−6.141+0.827MPV+5.613MLR-0.005PLR-0.346UBC.The combination was more valuable on predicting schizophrenia in acute stage (AUC 0.831, 95%CI 0.825 to 0.837). Conclusion: It was found that the protection effect on acute schizophrenia of UCB is indirect affection of the proinflammatory processes. Our findings suggest that a combination of MLR, MPV, PLR, UBC could be used to predict acute stage of schizophrenia.